The Shadow of the Passion: Protestants and the Suffering Christ in Nineteenth-Century British Art and Text - Janes, Dominic (IKON, 2008)
Abstract The British Pre-Raphaelite movement of the mid-nineteenth century produced a wide range of innovative art. Amongst these works were a number that were conspicuous for their use of religious imagery that the native Protestant majority regarded with suspicion as having been inspired by Catholic devotional imagery. Holman Hunt (1827-1910) was notable in his desire to employ paint in the service of Protestant faith. He attempted to find ways to paint images that made reference to the Crucifixion in ways which were educational and inspirational. Since the Crucifixion itself was widely understood to be not simply the subject of symbolic depiction in the Catholic Church but also of idolatrous devotion he disguised his imagery. This had the further advantage of avoiding controversy in the light of contemporary social attitudes which were sensitive to the depiction of male nakedness and suffering. This can be understood to derive from a fear that depictions of physical abuse were degrading rather than redemptive. This attitude is not confined to nineteenth-century Britain, but underlies, for instance, much of the recent controversy towards the director Mel Gibson’s film, The Passion of the Christ (2004). This case study highlights some of the problems in the depiction and reception of Christological iconography of self-sacrifice in countries in which Protestantism is culturally dominant.